Impact Assessment of Groundwater Quality using WQI and Geospatial tools: A Case Study of Islamkot, Tharparkar, Pakistan - Kumar, N.; Mahessar, A. A.; Memon, S. A.; Ansari, K.; Qureshi, A. L. (Engineering, Technology & Applied Science Research, 2020)
Groundwater is the only source of fresh water in the Thar Desert which is located in an arid region of Pakistan with dense population and spreads over 19,638km2. Low rainfall, low groundwater recharge, high evaporation and absence of perennial streams are the general reasons for water scarcity. Being the single water source for drinking, domestic and industrial uses, and livestock activities, this source is highly overexploited. Realizing the gravity of the situation, this paper presents a groundwater quality evaluation of Islamkot, Tharparkar, using Water Quality Index (WQI) and Geospatial tools. 40 samples were collected from dug wells. The TDS of 28 samples was found higher than 3000mg/L and 12 samples ranged from 1500 to 3000mg/L. Many (28) samples were not further analyzed due to their very high TDS which made the water unfit for drinking. Twelve samples with TDS ranging from 1500 to 3000 mg/L were further analyzed. The analyzed results revealed the average values of pH, EC, TDS, salinity, chloride, total alkalinity, fluoride, and arsenic. The results did not meet NEQS and WHO guidelines. Pearson correlation analysis was conducted among parameters. Further, groundwater quality was assessed by WQI and indicated that water quality varied from very poor to unsuitable for drinking. The consumption of polluted groundwater has been the main cause of prevalent waterborne diseases and poses a very high risk for public health